2002
DOI: 10.4315/0362-028x-65.2.260
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Acid Adaptation on the Tolerance of Escherichia coli O157:H7 to Some Subsequent Stresses

Abstract: Three stains of Escherichia coli O157:H7, including ATCC 43889, ATCC 43895, and 933, were first subjected to acid adaptation at a pH of 5.0 for 4 h. Thermal tolerance at 52 degrees C and survival of the acid-adapted as well as the nonadapted cells of E. coli O157:H7 in the presence of 10% sodium chloride, 0.85% bile salt, or 15.0% ethanol were investigated. Results showed that the effect of acid adaptation on the survival of E. coli O157:H7 varied with the strains and types of subsequent stress. Acid adaptatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…This difference may, again, be attributed to the protective effects of the increasing electrical conductivity induced by the addition of the sodium and potassium salts. The addition of preservatives þ 2.7% citric acid effected greater injury (100%) in E. coli 35218 than occurred in the acid-resistant enterohemorrhagic E. coli (96%), which may be attributed to the acid-resistant nature of E. coli O157:H7 (Cheng et al, 2002;Duffy et al, 1999;Marshall et al, 2005Yu et al, 2001. …”
Section: Injury Of E Coli O157:h7 and Non-pathogenic E Coli By Pefmentioning
confidence: 98%
See 1 more Smart Citation
“…This difference may, again, be attributed to the protective effects of the increasing electrical conductivity induced by the addition of the sodium and potassium salts. The addition of preservatives þ 2.7% citric acid effected greater injury (100%) in E. coli 35218 than occurred in the acid-resistant enterohemorrhagic E. coli (96%), which may be attributed to the acid-resistant nature of E. coli O157:H7 (Cheng et al, 2002;Duffy et al, 1999;Marshall et al, 2005Yu et al, 2001. …”
Section: Injury Of E Coli O157:h7 and Non-pathogenic E Coli By Pefmentioning
confidence: 98%
“…E. coli O157:H7 in juice with antimicrobials and 2.7% citric acid (pH 2.7) treated with PEF was reduced by 2.60, 4.32 and 6.95 log CFU/ml at 45, 50 and 55 C while the surrogate E. coli decreased by 3.54, 5.69, and 7.13 log, under the same conditions. The acid-resistant nature inherent to many strains of E. coli O157:H7, including our strain, ATCC 34895 may have contributed to its greater survivability in strawberry juice þ 2.7% citric acid (pH 2.71, Table 1) when treated by PEF at 45 and 50 C (Cheng et al, 2002;Yu et al, 2001).…”
Section: Inactivation Of E Coli O157:h7 and Non-pathogenic E Coli Bmentioning
confidence: 99%
“…In the United States, the bacterium causes an estimated 73,000 cases of infection per year, with up to 61 deaths (32), and several large outbreaks have occurred worldwide (33,34). E. coli O157:H7 is a highly virulent pathogen because it carries genes for Shiga toxin production and has an adaptive acid tolerance response system that results in strong acid resistance (35)(36)(37). Therefore, we selected E. coli O157:H7 as the target pathogen for study of the bactericidal effects of natural acidic compounds.…”
mentioning
confidence: 99%
“…Moreover, it is suggested that the recovery of bacteria in bile cultures is affected by toxicity of bile salts. Thus, traditional culturing methods of bile might miss a large number of underlying bacterial infections that could lead to acute or chronic cholecystitis (Grill et al, 2000;Cheng et al, 2002;De Boever and Verstraete, 1999;Kurtin et al, 2000;Manolis et al, 2008). Culture of bile from the gallbladder of patients with uncomplicated cholelithiasis during cholecystectomy has shown principally E. coli.…”
Section: Author(s) Agree That This Article Remains Permanently Open Amentioning
confidence: 99%